Gas-to-liquid: A viable alternative to oil-derived transport fuels? - Craig Brown (The Oxford Institute for Energy Studies, 2013)
A number of high-profile projects and a wave of recent investments have focused attention on the global gas-to-liquid (GTL) industry, suggesting a latent potential for gas-to-liquid fuels to usher in a new conceptualization of oil product markets. The clean-burning, high-quality characteristics of GTL diesel fuels lend support to this outlook, seemingly offering a viable substitute to oil-derived diesel in the global transport sector. However, doubts over the long-term viability of large-capacity GTL projects in the absence of heavily subsidized gas feedstock prices leads to an alternative narrative, suggesting that GTL products will have only a limited impact in the global transport sector by virtue of the industry's unsustainable growth potential. Evidence of this is seen in Europe, where despite the favourable market conditions for diesel imports, GTL diesel remains a niche product with relatively narrow commercial applications. As such, the recent wave of GTL investments may not be totally justified by market context, and the potential for GTL fuels to impact oil product markets may be overstated.
Keywords: 330; GTL; diesel; blend stock; transport fuel; natural gas substitution; downstream refining; Fischer-Tropsch